INTERNALISASI UNDANG-UNDANG 35 TAHUN 2009 TENTANG NARKOTIKA TERHADAP ANGGOTA KEPOLISIAN DAERAH JAWA BARAT (Jurnal De Jure Muhammadiyah Cirebon, 2022)
The Narcotics Law number 35 of 2009 was invited on October 12 of 2009 by President Doctor Susilo Bambang Yudoyono, promulgated by the Menkumham Andi Mattalata recorded in the State Gazette of the Republic of Indonesia of 2009 number 143, and an explanation of Law number 35 of 2009 is placed on The State Gazette of the Republic of Indonesia number 5062 all Indonesian citizens must know it. The National Police of the Republic of Indonesia, especially the West Java Region in accordance with Police Regulation Number 14 of 2018 concerning the Organizational Structure of Governance at the Regional Police level and the Narcotics Investigation Directorate headed by a Director, Deputy Director, Operational Development Section, Investigation Supervision Section and Sub Directorates have duties and authorities carry out investigations and investigations into criminal acts of drug abuse, including counseling, guidance, prevention and rehabilitation of victims of drug abuse. Cases of drug abuse carried out by members of the Police in West Java each year have increased both as dealers, dealers and as users, starting from the rank of enlisted to the level of middle-ranking officers and the perpetrators are not only members of the Police. Male Polwan also exist as victims of drug abuse. Many members of the Police who have been entangled in drug abuse have been brought to the general court and have been sanctioned by the Police Code of Ethics with various punishments, either serving prison sentences or being fired as members of the Police. The internalization of law number 35 of 2009 carried out by the Directorate of Narcotics Investigation has been carried out in accordance with its authority both in general and specifically for members of the National Police and their families (Bhayangkari), from the Polda level to the Polsek level, but due to a lack of understanding of the law This is about the impact and consequences that arise as well as the weak foundation of faith from each member who is entangled in drug abuse so that it is a sign that they are aware that they have fallen into a drug trap that is difficult to release. The role of the family is very necessary to support personnel who are entangled in drugs in sensitizing bad behavior that is entangled in drug abuse but the most important thing is awareness, understanding, especially the laws that govern it, about the consequences that occur not only for themselves but also the families of co-workers and superiors of members of the National Police. itself as well as the National Police Institution as an instrument of the State for law enforcement.Keywords: Internalization, Police, Drugs.